Erratum: Rice Sufficiency Officers’ Role Perception and Job Satisfaction as Agricultural Research and Extension Workers - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Tanzo, I. R., & Yusongco, C. G. (2014). Rice Sufficiency Officers’ Role Perception and Job Satisfaction as Agricultural Research and Extension Workers. Journal of International Agricultural and Extension Education, 21(2), 72-82” was incorrect as published. The correct DOI is: 10.4148/2831-5960.1233